Autoubiquitination of the Hrd1 Ligase Triggers Protein Retrotranslocation in ERAD - Baldridge, Ryan D; Rapoport, Tom A (Cell, 2016)
Misfolded proteins of the ER are retrotranslocated to the cytosol, where they are polyubiquitinated, extracted from the membrane, and degraded by the proteasome. To investigate how the ER-associated Degradation (ERAD) machinery can accomplish retrotranslocation of a misfolded luminal protein domain across a lipid bilayer, we have reconstituted retrotranslocation with purified S. cerevisiae proteins, using proteoliposomes containing the multi-spanning ubiquitin ligase Hrd1. Retrotranslocation of the luminal domain of a membrane-spanning substrate is triggered by autoubiquitination of Hrd1. Substrate ubiquitination is a subsequent event, and the Cdc48 ATPase that completes substrate extraction from the membrane is not required for retrotranslocation. Ubiquitination of lysines in Hrd1's RING-finger domain is required for substrate retrotranslocation in vitro and for ERAD in vivo. Our results suggest that Hrd1 forms a ubiquitin-gated protein-conducting channel.